The Application of Social Responsibility in Enterprises - Hu, Yuqiu; Ding, Xinyu (International Journal of Global Economics and Management, 2024)
Taking the initiative to assume social responsibility is not only the basic content of entrepreneurship, but also an important force to promote social progress. Based on the theory of corporate social responsibility, this thesis studies human resource management. First of all, from the perspective of corporate social responsibility, this project analyzes the problems existing in the implementation of CSR, that is, how to coordinate the economic benefits and social responsibility of enterprises, how to carry out effective supervision and evaluation, and how to participate in and communicate with employees. Secondly, it expounds the theoretical basis of CSR, analyzes the significance of CSR to HR, and gives corresponding countermeasures and suggestions, so as to provide certain theoretical support and practical guidance for Chinese enterprises to apply CSR to HR management.